(untitled) (Comparative Professional Pedagogy, 2021)
The paper focuses on the process of internationalization of higher education in Germany as one of the factors that ensures international cooperation in education and science, strengthens competition in the global educational market, improves the quality of future professionals’ training. The study considers the specific features of joint degree programs for training Ph.D. students in German universities and reviews three main types of these programs, namely: a research project within a pre-defined research topic; previously developed schemes of academic cooperation; the program of obtaining a joint Ph.D. degree in universities of the doctoral student’s choice (which do not yet have a formal cooperation agreement). It was found that joint degree programs provide the prospective Doctors of Philosophy with the opportunity to conduct their doctoral studies in two universities. The training plan is developed jointly by two or more higher education or research institutions, so that doctoral students are enabled to conduct research based on several universities or research institutions, while receiving simultaneous scientific consulting from several experienced scientists. It was determined that these programs stimulate mobility and intercultural exchange, significantly increase the competitiveness of their graduates, promote greater transparency and alignment of curricula through mutual recognition of scientific degrees, as well as the establishment of close inter-academic contacts. Key institutions promoting and coordinating the development of the internationalization of higher education in Germany include the Federal Ministry of Education and Research (BMBF), the German Research Foundation (DFG), the German Rectors’ Conference (HRK), the German Academic Exchange Service (DAAD), Alexander von Humboldt Foundation (AvH), and others.